Tubulin βII and βIII Isoforms as the Regulators of VDAC Channel Permeability in Health and Disease - Puurand, Marju (Cells, 2019)
In recent decades, there have been several models describing the relationships between the cytoskeleton and the bioenergetic function of the cell. The main player in these models is the voltage-dependent anion channel (VDAC), located in the mitochondrial outer membrane. Most metabolites including respiratory substrates, ADP, and Pi enter mitochondria only through VDAC. At the same time, high-energy phosphates are channeled out and directed to cellular energy transfer networks. Regulation of these energy fluxes is controlled by β-tubulin, bound to VDAC. It is also thought that β-tubulin‒VDAC interaction modulates cellular energy metabolism in cancer, e.g., switching from oxidative phosphorylation to glycolysis. In this review we focus on the described roles of unpolymerized αβ-tubulin heterodimers in regulating VDAC permeability for adenine nucleotides and cellular bioenergetics. We introduce the Mitochondrial Interactosome model and the function of the βII-tubulin subunit in this model in muscle cells and brain synaptosomes, and also consider the role of βIII-tubulin in cancer cells.